2016
DOI: 10.1093/scan/nsw138
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin conditions trait-based rule adherence

Abstract: Rules, whether in the form of norms, taboos or laws, regulate and coordinate human life. Some rules, however, are arbitrary and adhering to them can be personally costly. Rigidly sticking to such rules can be considered maladaptive. Here, we test whether, at the neurobiological level, (mal)adaptive rule adherence is reduced by oxytocin—a hypothalamic neuropeptide that biases the biobehavioural approach-avoidance system. Participants (N = 139) self-administered oxytocin or placebo intranasally, and reported the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…Indeed, the oxytocin system has been shown to influence a range of non-social animal behaviors including learning [70], location preference [71], and pain tolerance [72]. Human research has also demonstrated that oxytocin administration reduces amygdala activation during pain stimulation [73] and decreases trait-based rule adherence [74]. Despite that fact we did not collect data explicitly reflecting approach-related behaviors, the data in the current study is consistent with increasing evidence that oxytocin increases both social and non-social-approach-related behaviors [64].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the oxytocin system has been shown to influence a range of non-social animal behaviors including learning [70], location preference [71], and pain tolerance [72]. Human research has also demonstrated that oxytocin administration reduces amygdala activation during pain stimulation [73] and decreases trait-based rule adherence [74]. Despite that fact we did not collect data explicitly reflecting approach-related behaviors, the data in the current study is consistent with increasing evidence that oxytocin increases both social and non-social-approach-related behaviors [64].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen of the studies included male and female participants (27, 29, 33, 37, 4042, 46, 48, 54, 56, 59, 60, 62). Two studies included only female participants (31, 47).…”
Section: Resultsmentioning
confidence: 99%
“…Under OT participants violated the rule more often. This was most apparent in individuals who had a high need for structure (46).…”
Section: Studies In Healthy Participantsmentioning
confidence: 99%
“…Similarly, people differ in cheating rates and their willingness to lie for profit ( Heck et al, 2018 ; Hilbig & Zettler, 2015 ). These disparate findings combined suggest that people systematically differ in the value they derive from abiding by rules and/or the disutility incurred when violating rules ( Gross & De Dreu, 2017 ; Kashy & DePaulo, 1996 ; Kimbrough & Vostroknutov, 2016 , 2018 ). Indeed, others before us have shown that individual differences that are conceptually or empirically related to rule following, such as guilt proneness and honesty–humility, correlate with ethical conduct and shying away from delinquent behavior ( Fleeson et al, 2014 ; Heck et al, 2018 ; Hilbig & Zettler, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whether we consider work on obedience to authority ( Milgram, 1963 ), social conformity and norm compliance ( Stubbersfield et al, 2019 ), or adherence to culture-specific rules such as “wait until the light turns green,” or “thou shall not cheat” ( Gelfand et al, 2011 ), people often abide by rules. It has been argued that deviations from rules generate a psychological cost ( Abeler et al, 2014 ; Gross & De Dreu, 2017 ; Kimbrough & Vostroknutov, 2016 , 2018 ; Krupka & Weber, 2013 ) and create a cognitive conflict between what one should and wants to do ( Pfister et al, 2019 ; Schelling, 1984 ).…”
Section: Introductionmentioning
confidence: 99%